Identification of novel candidate pathogenic genes in pituitary stalk interruption syndrome by whole‐exome sequencing. Issue 20 (31st August 2020) - Fang, Xuqian; Zhang, Yuwen; Cai, Jialin; Lu, Tingwei; Hu, Junjie; Yuan, Fei; Chen, Peizhan
Abstract: Pituitary stalk interruption syndrome (PSIS) is a type of congenital malformation of the anterior pituitary, which leads to isolated growth hormone deficiency or multiple hypothalamic‐pituitary deficiencies. Many genetic factors have been explored, but they only account for a minority of the genetic aetiology. To identify novel PSIS pathogenic genes, we conducted whole‐exome sequencing with 59 sporadic PSIS patients, followed by filtering gene panels involved in pituitary development, holoprosencephaly and midline abnormality. A total of 81 heterozygous variants, distributed among 59 genes, were identified in 50 patients, with 31 patients carrying polygenic variants. Fourteen of the 59 pathogenic genes clustered to the Hedgehog pathway. Of them, PTCH1 and PTCH2, inhibitors of Hedgehog signalling, showed the most frequent heterozygous mutations (22%, seven missense and one frameshift mutations were identified in 13 patients). Moreover, five novel heterozygous null variants in genes including PTCH2 (p.S391fs, combined with p.L104P), Hedgehog acyltransferase (p.R280X, de novo), MAPK3 (p.H50fs), EGR4 (p.G22fs, combined with LHX4 p.S263N) and SPG11 (p.Q1624X), which lead to truncated proteins, were identified. In conclusion, genetic mutations in the Hedgehog signalling pathway might underlie the complex polygenic background of PSIS, and the findings of our study could extend the understanding of PSIS pathogenic genes.